2008
DOI: 10.1136/jmg.2008.059915
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation within European carriers of the Y-chromosomal gr/gr deletion is independent of Y-chromosomal background

Abstract: The phenotypic variation of gr/gr carriers in men of European origin is largely independent of the Y-chromosomal background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 29 publications
12
77
2
Order By: Relevance
“…In the present study, we observed that not all men with AZFc subdeletions had the expected deletion of DAZ and CDY1 gene copies. As reported previously [36], there were several men who had DAZ and/or CDY1 gene copies intact despite having gr/gr, b1/b3 or b2/b3 deletion. To determine the impact of the DAZ and CDY1 copy deletions, we classified the men with AZFc subdeletions (gr/gr, b1/b3 and b2/b3) based on the DAZ and CDY1 gene copies deleted.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the present study, we observed that not all men with AZFc subdeletions had the expected deletion of DAZ and CDY1 gene copies. As reported previously [36], there were several men who had DAZ and/or CDY1 gene copies intact despite having gr/gr, b1/b3 or b2/b3 deletion. To determine the impact of the DAZ and CDY1 copy deletions, we classified the men with AZFc subdeletions (gr/gr, b1/b3 and b2/b3) based on the DAZ and CDY1 gene copies deleted.…”
Section: Discussionsupporting
confidence: 70%
“…Thus based on this analysis we could argue that the sY1291/sY1191 based screening strategy might be associated with false detections. Indeed based on a similar strategy, Krausz et al, reported a false deletion rate of 5.3 % [36]; in the present study it was calculated as 19.4 % (14/72). This was not due to PCR failures as a biplex reaction was optimized where the housekeeping SRY was always co-amplified.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…38,39 The majority of gr/gr deletion carriers belonged, as expected, to the P,Q,R branches in both patients and controls, supporting that the phenotypic variability of gr/gr deletion is independent of Y-chromosomal background in Europeans. 40 Interestingly, we found b2/b3 deletion only in the patient cohort (4/296; 1.3%) and only one carrier belonged to hgr N and thus had the constitutive b2/b3 deletion. The remaining three b2/b3 deletion carriers belonged to hrgs C,F,G,H,I, which is a frequent Y hgr in Moroccan population for which b2/b3 deletion has been recently reported in association with male infertility.…”
Section: -124mentioning
confidence: 62%
“…59 However, given a 5% false deletion rate detected in a recent multicenter study, 63 deletions should be confirmed by gene dosage analysis. 63,64 There are mainly two reasons for gr/gr deletion testing in infertile men: i) the deletion contributes to the etiopathogenesis of impaired sperm production since it is able to influence the spermatogenic potential of the carrier; ii) the couple should be aware that the deletion (i.e. a genetic risk factor for impaired sperm production) will be obligatorily transmitted to their male offspring and the deletion may become complete AZFc deletion (i.e.…”
Section: Gr/gr Deletionmentioning
confidence: 99%